(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, the chemical composition of pomegranate juice was examined using ultraviolet and infrared radiation to obtain additional information on the characteristics of electroflotation processes. improvement of working technology and improvement of the quality of produced pomegranate juice is based on the application of electrophysical methods.